Akal Budi sebagai Pilar Etika dan Spiritualitas: Telaah Filsafat Kontemporer - Agustin Nadiya Kusumawati; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2025)
This study aims to explore the urgency of reason and conscience (akal budi) in modern life through a content analysis of the Endgame podcast episode titled